1973
DOI: 10.1111/j.1432-1033.1973.tb02996.x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Processing of Ribosomal RNA in Cultured Plant Cells

Abstract: Four species of rapidly labelled, high-molecular-weight RNA have been extracted from partially purified nuclei of cultured sycamore cells. The molecular weights of these RNA species RNA is consistent with the sequence of reacttiom shown above, and has also demonstrated that methylation is confined to the rRNA sequences of the 45-8 RNA [6].I n other eukaryotes details of the processing of the precursors of rRNA are less well understood. The large 45-S precursor appears to be peculiar to mammals, and it has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

1974
1974
1987
1987

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 29 publications
1
17
1
Order By: Relevance
“…The incorporation of [3H]UTP in nuclei in vitro is thought to represent the additional elongation of RNA chains that were growing in vivo, but became arrested during the isolation of nuclei [14,16]. In our present experiment, this is indicated by the fact that while the average length of nascent portions of RNA chains in terms of [3H]UMP/[3H]uridine ratio ranges between 50 and 135 nucleotides, estimation of the average molecular weight of labelled RNA suggests the longer length of nucleotide chains (Fig.2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The incorporation of [3H]UTP in nuclei in vitro is thought to represent the additional elongation of RNA chains that were growing in vivo, but became arrested during the isolation of nuclei [14,16]. In our present experiment, this is indicated by the fact that while the average length of nascent portions of RNA chains in terms of [3H]UMP/[3H]uridine ratio ranges between 50 and 135 nucleotides, estimation of the average molecular weight of labelled RNA suggests the longer length of nucleotide chains (Fig.2).…”
Section: Discussionmentioning
confidence: 99%
“…RNA was extracted from nuclei and precipitated by cetyltrimethylammonium bromide [ 151, essentially as described by Cox [16]. RNA polymerase B reaction was allowed to proceed for 40min in the medium scaled up to 2.0 ml, and terminated by freezing the mixture at -80 "C. After the addition of 100 pg of deoxyribonuclease I and 40 pl of 250 mM MgClz, the mix was thawed, kept at 0-4 "C for 5 min, and adjusted to 0.1 % with respect to sodium dodecylsulphate.…”
Section: Isolation Of Rnafrom Nucleimentioning
confidence: 99%
See 1 more Smart Citation
“…These interactions may result in activation or inhibition of enzyme activity [36]. For example, heparin inhibits the activity of some enzymes such as lysosomal hydrolases [36], DNA polymerase [37], RNA polymerase [38], ribonuclease [39], ornithine decarboxylase [40] and casein kinase I1 [41,421. Other enzymes are activated by heparin, such as lipoprotein lipase [43], tyrosine hydroxylase [44], rabbit skeletal muscle and rat liver phosphorylase kinase [45,461 and the p68 kinase.…”
Section: The Signgicance Of' the P68 Kinase Activation By Heparinmentioning
confidence: 99%
“…Certainly, a significant proportion of this increased synthesis of rRNA in response to auxin relates to increased levels of RNA polymerase I enzyme and to increased activity of those RNA polymerase I molecules (1 1). Since mature rRNAs (1 8S and 25S or 0.7 and 1.3 x 106 D, respectively) are initially transcribed as a large precursor molecule of about 2.8 x 105 D in some plants (8,17,25) and about 2.3 x 106 in others (6, 28) including soybean (15), the rate of processing of these large transcripts could be involved in establishing the rate of accumulation of new ribosomes. Melanson and Ingle (23) in fact have reported that precursor processing, including a large increase in the rate of processing of the 1.4 x 106 precursor into the mature 1.3 x 106 (25S) rRNA, accounts for a part of the auxin-enhanced synthesis and accumulaton of ribosomes in artichoke tissue.…”
Section: Discussionmentioning
confidence: 99%